A genetically based ecological trade‐off contributes to setting a geographic range limit. (11th October 2021) - Mauro, Alexander A.; Torres‐Dowdall, Julián; Marshall, Craig A.; Ghalambor, Cameron K.
Abstract: Understanding the ecological factors that shape geographic range limits and the evolutionary constraints that prevent populations from adaptively evolving beyond these limits is an unresolved question. Here, we investigated why the euryhaline fish, Poecila reticulata, is confined to freshwater within its native range, despite being tolerant of brackish water. We hypothesised that competitive interactions with a close relative, Poecilia picta, in brackish water prevents P . reticulata from colonising brackish water. Using a combination of field transplant, common garden breeding, and laboratory behaviour experiments, we find support for this hypothesis, as P . reticulata are behaviourally subordinate and have lower survival in brackish water with P . picta . We also found a negative genetic correlation between P . reticulata growth in brackish water versus freshwater in the presence of P . picta, suggesting a genetically based trade‐off between salinity tolerance and competitive ability could constrain adaptive evolution at the range limit. Abstract : Understanding the ecological factors that shape geographic range limits and the evolutionary constraints that prevent populations from adaptively evolving beyond these limits is an unresolved question. Here, we investigated why the euryhaline fish, Poecila reticulata, is confined to freshwater within its native range, despite being tolerant of brackish water.